Scalability of spheroid-derived small extracellular vesicles production in stirred systems - Dauphin, Thibaud; de Beaurepaire, Laurence; Salama, Apolline; Pruvost, Quentin; Claire, Clémentine; Haurogné, Karine; Sourice, Sophie; Dupont, Aurélien; Bach, Jean-Marie; Hervé, Julie; Olmos, Eric; Bosch, Steffi; et al. (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionSmall extracellular vesicle (sEV)-based therapies have gained widespread interest, but challenges persist to ensure standardization and high-scale production. Implementing upstream processes in a chemically defined media in stirred-tank bioreactors (STBr) is mandatory to closely control the cell environment, and to scale-up production, but it remains a significant challenge for anchorage-dependent cells.MethodsWe used a human β cell line, grown as monolayer or in suspension as spheroid in stirred systems. We assessed the consequences of culturing these cells in 3D with, or without fetal bovine serum in a chemically defined medium, for cell growth, viability and metabolism. We next explored how different scale-up strategies might influence cell and spheroid formation in spinner flask, with the aim to transfer the process in instrumented Ambr®250 STBr. Lastly, we analyzed and characterized sEV production in monolayer, spinner flask and STBr.Results and discussionGeneration of spheroids in a chemically defined medium allowed the culture of highly viable cells in suspension in stirred systems. Spheroid size depended on the system’s volumetric power input (P/V), and maintaining this parameter constant during scale-up proved to be the optimal strategy for standardizing the process. However, transferring the spinner flask (SpF) process to the Ambr®250 STBr at constant P/V modified spheroid size, due to important geometric differences and impeller design. Compared to a monolayer reference process, sEV yield decreased two-fold in SpF, but increased two-fold in STBr. Additionally, a lower expression of the CD63 tetraspanin was observed in sEV produced in both stirred systems, suggesting a reduced release of exosomes compared to ectosomes. This study addresses the main issues encountered in spheroid culture scale-up in stirred systems, rather conducive for the production of ectosomes.